Knowledge-driven feature engineering to detect multiple symptoms using ambulatory blood pressure monitoring data. (April 2022) - Janjua, Zaffar Haider; Kerins, David; O'Flynn, Brendan; Tedesco, Salvatore
Highlights: Ambulatory blood pressure monitoring is important to avoid the "white coat effect". Multiple symptoms detection is important for the proper diagnosis of the disorder. Knowledge-driven features can reduce machine learning model complexity. Adding knowledge to features fine-tunes model for accurate disorder detection. Random Forest efficiently detected multiple symptoms using knowledge-driven features. Abstract: Background: Hypertension is a major health concern across the globe and needs to be properly diagnosed to so it can be treated and to mitigate for this critical health condition. In this context, ambulatory blood pressure monitoring is essential to provide for a proper diagnosis of hypertension, which may not be possible otherwise due to the white coat effect or masked hypertension. In this paper, the objective is to develop a model which incorporates expert's knowledge in the feature engineering process so as to accurately predict multiple medical conditions. As a case study, we have considered multiple symptoms related to hypertension and used an ambulatory blood pressure monitoring method to continuously acquire hypertension relevant data from a patient. The goal is to train a model with a minimum set of the most effective knowledge-driven features which are useful to detect multiple symptoms simultaneously using multi-class classification techniques. Method: Artificial intelligence-based blood pressure monitoring techniques introduce a new dimension in the diagnosis of hypertension by enabling a continuous (24hours) analysis of systolic and diastolic blood pressure levels. In this work, we present a model that entails a knowledge-driven feature engineering method and implemented an ambulatory blood pressure monitoring system to diagnose multiple cardiac parameters and associated conditions simultaneously these include morning surge, circadian rhythm, and pulse pressure. The knowledge-driven features are extracted to improve the interpretability of the classification model and machine learning techniques (Random Forest, Naive Bayes, and KNN) were applied in a multi-label classification setup using RAkEL to classify multiple conditions simultaneously. Results: The results obtained (F 1 = 0.918) show that the Random forest technique has performed well for multilabel classification using knowledge-driven features. Our technique has also reduced the complexity of the model by reducing the number of features required to train a machine learning model. Conclusion: Considering these results, we conclude that knowledge-driven feature engineering enhances the learning process by reducing the number of features given as input to the machine learning algorithm. The proposed feature engineering method considers expert's knowledge to develop better diagnosis models which are free from misleading data-driven noisy features in some situations. It is a white-box approach in which clinicians can under stand the importance of a feature while looking at its value.